Induced cardiac pacemaker cells survive metabolic stress owing to their low metabolic demand - Gu, Jin-mo (Exp Mol Med, 2019)
Cardiac pacemaker cells of the sinoatrial node initiate each and every heartbeat. Compared with our understanding of the constituents of their electrical excitation, little is known about the metabolic underpinnings that drive the automaticity of pacemaker myocytes. This lack is largely owing to the scarcity of native cardiac pacemaker myocytes. Here, we take advantage of induced pacemaker myocytes generated by TBX18-mediated reprogramming (TBX18-iPMs) to investigate comparative differences in the metabolic program between pacemaker myocytes and working cardiomyocytes. TBX18-iPMs were more resistant to metabolic stresses, exhibiting higher cell viability upon oxidative stress. TBX18-induced pacemaker myocytes (iPMs) expensed a lower degree of oxidative phosphorylation and displayed a smaller capacity for glycolysis compared with control ventricular myocytes. Furthermore, the mitochondria were smaller in TBX18-iPMs than in the control. We reasoned that a shift in the balance between mitochondrial fusion and fission was responsible for the smaller mitochondria observed in TBX18-iPMs. We identified a mitochondrial inner membrane fusion protein, Opa1, as one of the key mediators of this process and demonstrated that the suppression of Opa1 expression increases the rate of synchronous automaticity in TBX18-iPMs. Taken together, our data demonstrate that TBX18-iPMs exhibit a low metabolic demand that matches their mitochondrial morphology and ability to withstand metabolic insult.